2008
DOI: 10.4049/jimmunol.180.5.2805
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal MHC Ib-Restricted CD8+ T Cells Undergo Homeostatic Expansion in the Absence of Conventional MHC-Restricted T Cells

Abstract: Naive T cells have the capacity to expand in a lymphopenic environment in a process called homeostatic expansion, where they gain a memory-like phenotype. Homeostatic expansion is dependent on competition for a number of factors, including growth factors and interactions with their selecting self-MHC molecules. In contrast to conventional T cells, it is unclear whether class Ib-restricted CD8+ T cells have a capacity to undergo homeostatic expansion. In this study, we demonstrate that polyclonal MHC Ib-restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 79 publications
0
12
1
Order By: Relevance
“…However, in these animals, we observed substantially increased proliferation of the transferred memory CD8 T cells, compared with even normal WT animals (data not shown). This increase in division closely mirrored the rapid proliferation observed when cells (naive or memory) are adoptively transferred into lymphopenic environments, rather than the slow, continuous homeostatic turnover observed under normal steadystate conditions (33,55,56). Therefore, we limited our analysis to WT, CD4 2/2 , and MHC II 2/2 animals.…”
Section: Discussionmentioning
confidence: 96%
“…However, in these animals, we observed substantially increased proliferation of the transferred memory CD8 T cells, compared with even normal WT animals (data not shown). This increase in division closely mirrored the rapid proliferation observed when cells (naive or memory) are adoptively transferred into lymphopenic environments, rather than the slow, continuous homeostatic turnover observed under normal steadystate conditions (33,55,56). Therefore, we limited our analysis to WT, CD4 2/2 , and MHC II 2/2 animals.…”
Section: Discussionmentioning
confidence: 96%
“…K b−/− D b−/− mice were backcrossed to C57BL/6 mice for 10 generations and were obtained from Taconic Farm (40). K b−/− D b−/− CIITA −/− mice and K b−/− D b−/− ®2M −/− mice were generated by crossing K b−/− D b−/− mice with either CIITA −/− mice or ®2M −/− mice (37). B6.129S6-H2-T23 tm1Cant /J mice, which are Qa-1 −/− , were a gift from Dr. Harvey Cantor (Harvard).…”
Section: Methodsmentioning
confidence: 99%
“…However, class Ib-restricted T cells expand to relatively large populations in the secondary lymphoid organs of K b−/− D b−/− CIITA −/− mice that lack conventional T cells selected by MHC class Ia or class II molecules (37). These mice provide an interesting model to study the potential role of class Ib-restricted T cells in virus infections.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that deletion of MHCII could result in the accumulation of CD44 + CD8 + memory T cells [31]; therefore, we were interested in determining whether the lamina propria Tc17 cells found in MHCII −/− →WT mice were CD44 positive. Using flow cytometry, we found that lamina propria IL-17 + CD8 + TCR-β + , FOXP3 + CD8 + TCR-β + , and IFN-γ + CD8 + TCR-β + isolated from MHCII −/− →WT mice were all positive for CD44, indicating these cells have a memory cell surface marker phenotype (Supporting Information Fig.…”
Section: Il-17 + and Foxp3 + Cd8 + T Cells Are Upregulated In The Cecmentioning
confidence: 99%
“…Similarly to what was observed in the lamina propria, there was a robust induction of both Tc17 and FOXP3 + CD8 + T cells (Fig. 4) in the IELs isolated from MHCII −/− →WT ceca compared to WT→WT counterparts, suggesting that these atypical CD8 + cells are upregulated throughout the entire mucosa.A previous study reported that deletion of MHCII could result in the accumulation of CD44 + CD8 + memory T cells [31]; therefore, we were interested in determining whether the lamina propria Tc17 cells found in MHCII −/− →WT mice were CD44 positive. Using flow cytometry, we found that lamina propria IL-17 + CD8 + TCR-β + , FOXP3 + CD8 + TCR-β + , and IFN-γ + CD8 + TCR-β + isolated from MHCII −/− →WT mice were all positive for CD44, indicating these cells have a memory cell surface marker phenotype (Supporting Information Fig.…”
mentioning
confidence: 99%